Evaluation Of Factors That Affect Acceptance Of Split Thickness Skin Graft (STSG) - Mori, Jayrajsinh; Naniwadekar, R. G.; Dodia, Dhara (Journal of Neonatal Surgery, 2025)
Background: Split thickness skin grafts (STSGs) remain a cornerstone in reconstructive and burn surgery due to their versatility and effectiveness. Despite their widespread application, variability in graft acceptance persists due to several patient and procedural factors. Methods: A prospective observational study was conducted at Krishna Institute of Medical Sciences, Karad, from May 2023 to December 2024. Thirty-five patients undergoing STSG were evaluated based on pre- and postoperative variables including age, comorbidities, addictions, and fixation techniques. Statistical analysis was performed using SPSS v20. Results: Patients under 35 years demonstrated the highest graft acceptance rates (p=0.033). Comorbidities, particularly diabetes mellitus, significantly reduced graft survival (p=0.027). Gender and addictions did not show statistically significant correlation with graft acceptance. Postoperative infection and fixation technique played substantial roles in graft outcomes. Conclusion: Age and systemic comorbidities are critical predictors of STSG acceptance. Proper patient selection, preoperative optimization, and infection control can enhance graft survival and patient outcomes.